مرايا الملوك: دراسة في ضوء نظرية الانساق الثقافية - العمري، رياض كريم عبدالله (الجامعة العراقية - مركز البحوث والدراسات الإسلامية, 2022)
تعد كتب مرايا الملوك من الموضوعات المهمة في تاريخ الفكر السياسي الإسلامي، بوصفها تتحدث عن نموذج معين من حيث المبدأ فهي تمثل دائرة السلاطين أو الحكام؛ ولكنها في الوقت نفسه كانت تحمل سمة الإعلامية والدعائية، بوصفها كتبا مطروحة لعامة الجماهير، وإنها نقلت وجهات النظر المرتبطة بالأحكام السلطانية من جهة، وما يرتبط بالجماهير من جهة ثانية بنحو يفترض أن يكون علميا ينبع من تصور ديني إلا أن البعد الدعائي قد يكون مستبطنا في الكثير من الكتابات، وهذا ما دعانا إلى أن نبحث في مسألة الكشف عن الانساق المضمرة في هذه الكتابات بوصفها تولدت ضمن سياق ثقافي معين من شأنه أن يضمر الكثير من الأفكار والأنساق المتوالدة جيلا بعد جيل ضمن دائرة فكرية معينة؛ لتصبح مهيمنة نسقية تجعل الناس يفكرون في ضوئها والتي تمثل مجموعة من الثوابت البنيوية أو الثوابت النسقية التي كانت حاكمة في إعطاء تصورات ومواقف قد ظهرت بنحو عبارات، أو لغة، أو مجاز، أو استعارات، أو كناية، أو اقتباس، أو طريقة من التأويل، التي تخفي الكثير من ذلك أو أنها تستبطن الكثير من ذلك الذي يمكن في ضوء هذه الدراسة الكشف عنها بالوقوف على طريقة التفكير التي سار على ضوئها النسق الفكري المتمثل بكتابات الأحكام السلطانية أو مرايا الملوك. The royal regulations, or what is referred to as the mirrors of the kings, is considered as one of the important subjects in the history of the political Islamic thought. In principle, they deal with a special model as they represent the closed circle of the royalty. At the same time, they are characterized with media and propaganda features as they are available in publicly feasible books. They involve viewpoints about the royal regulations. On the other hand, they tackle what is related to the population. This is supposed to be laid in a scientific way with a religious dimension, yet the propaganda one could be concealed in many writings. This is due to the fact that such writings have been derived from a specific cultural context. As a result, this could hide many thoughts and contexts which could come up by various generations through the course of time. This could take place within a specific cultural domain making it contextually dominant with many people considering them as a group of structural and contextual Constance. Such constancies we’re capable of determining views and ideas which conceal a lot of things presented by expressions, quotations, metaphor or a specific way of interpretation. The present study attempts to clarify this and supply an account of the manner of thinking which has been which has been adopted by the thinking context which is represented by the royal regulations, or the mirrors of the kings.
Keywords: التراث الديني -- الفكر الساسي الإسلامي -- الحكام القدامى -- الثوابت النسقية